USING TWO STAY TWO STRAY TO IMPROVE SPEAKING ABILITY AT SMK KHARISMA NUSANTARA - Anisa Fitriani; Iman Santoso (PROJECT (Professional Journal of English Education), 2022)
The aims of this research are : (1) to know the ability of students’ speaking skill in daily learning activity and (2) to increase students’ speaking ability at SMK Kharisma Nusantara through Two Stay Two Stray Technique. The researcher used Classroom Action Research as the method. This research was conducted on the first grade of Kharisma Nusantara Senior High School in the academic year of 2018/2019. This research divided into two cycles and seven meetings. The researcher took three meetings for test and four meetings for treatment. Each cycle covered the step of planning, acting, observing, and reflecting. Every meeting consisted greeting, main activity, and closing. In the first meeting of cycle 1, the researcher gave the pre-test to all students as the population. Through this pre-test, the researcher knew the students ability. The treatments of first cycle were in second meeting and was done in third meeting. And the last meeting of cycle 1, the students were given the post-test by the researcher. While, the researcher continued the research on cycle 2, which consist three meetings. Two metings for giving the treatment, and the last meting for the post-test. The result shows that learning English speaking can increase with Two Stay Two Stray Technique. The students can more active when they are speaking. Keywords:  Speaking Skill, Two Stay Two Stray (TSTS) , CAR